Neuropeptide S receptor gene (NPSR) and life events: G × E effects on anxiety sensitivity and its subdimensions. (January 2014) - Klauke, Benedikt; Deckert, Jürgen; Zwanzger, Peter; Baumann, Christian; Arolt, Volker; Pauli, Paul; Reif, Andreas; Domschke, Katharina
Abstract Objectives. The pathogenesis of anxiety is assumed to be interactively influenced by genetic and environmental factors. Thus, a gene–environment interaction (G × E) study of the neuropeptide S receptor gene (NPSR) A/T polymorphism (rs324981) and life events was conducted with respect to anxiety sensitivity (AS) as an intermediate phenotype of anxiety disorders. Methods. A sample of 475 healthy German subjects was genotyped for NPSR and assessed for AS, childhood maltreatment (CTQ) and recent life events (LTE). Influences on AS and its subdimensions were determined by a step-wise hierarchical regression and a multiple indicator multiple cause (MIMIC) model. Results. Significant main effects of NPSR and CTQ as well as significant G × E were observed, with T/T homozygosity and a high CTQ score resulting in increased anxiety sensitivity. MIMIC modelling yielded association of AS subfactor "concern about mental/cognitive incapacitation" and the basal somatic subdimension "concern about physical sensations" to be associated with CTQ and its interaction with NPSR, while the acute somatic subfactor "concern about heart/lung failure" was associated with NPSR and its interaction with LTE. Conclusions. Results indicate G × E effects of the more active NPSR rs324981 T allele and life events on AS with differential effects of temporally proximal and distal factors on specific AS subdimensions.